The privilege of peace - Huff, Tanya (Huff, Tanya. Peacekeeper novels, 2018)
When Big Yellow, the ship form of the plastic aliens responsible for the war, returns, Warden Torin Kerr is forced out of retirement to find a way to keep the peace.